(untitled) (Revista Puertorriqueña de Psicologia, 2016)
The Cirino System for Career Planning (Sistema Cirino de Planificación de Carreras) is a revision of the Cirino System for Occupational Planning. The new instrument ir more extensive and includes, in addition to occupational planning, leisure time and educational planning. The steps for completing the instrument were simplified.